O Curso de Etnodesenvolvimento e a formação diferenciada e intercultural: contribuições no contexto educacional, sociopolítico e cultural da Amazônia - PARENTE, Francilene de Aguiar (Universidade Federal do Paraná, 2022)
This article analyzes how the Ethnodevelopment course offered by the Universidade Federal do Pará [Federal University of Pará]/Altamira University Campus has contributed to the academic, political and professional training of students belonging to indigenous peoples and traditional communities in the context of the Amazon. It provides a descriptive-analytical approach to their experiences, starting with the process of the creation and organization of the course, based on affirmative public policies undertaken in Brazil, as well the course methodology and the challenges faced for the course to be implemented in the light of institutional issues. The reflections put forward show that the Ethnodevelopment course has contributed to expanding possibilities of action and political negotiation by these social agents based on their spaces of collective belonging, as well contributing to differentiated training that enables and instrumentalizes their inclusion as professionals in the field of education in the different territories of the Amazon region.